2013
DOI: 10.1021/cr3004955
|View full text |Cite
|
Sign up to set email alerts
|

Carbene Additions to Fullerenes

Abstract: CONTENTS 1. Introduction 7209 2. Carbene Addition to Empty Fullerenes 7210 2.1. Dihalocarbenes 7210 2.1.1. Dihalocarbene Additions to C 60 7210 2.1.2. Dihalocarbene Additions to C 70 7212 2.1.3. Dihalocarbene Additions to Fullerene Fragments 7213 2.2. Decomposition of Diazo Compounds 7215 2.2.1. Thermolysis of Diazo Compounds 7215 2.2.2. Photolysis of Diazo Compounds 7223 2.2.3. In-Situ Generation of Diazo Compounds 7223 2.2.4. Isomerization of Fulleroids to Methanofullerenes 7228 2.3. Decomposition of Diaziri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
111
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 425 publications
(766 reference statements)
0
111
0
Order By: Relevance
“…288−295 In general, these reactions are carried out thermally, and reactions with C 60 fullerene result in a mixture of three regioisomers, identified as the [6,6]-closed methanofullerene and the two [5,6]-open fulleroids. 296 Recently, Tuktarov and co-workers investigated cycloaddition of diazothioates to C 60 under thermal and catalytic conditions. 295 It was found that, in the presence of a palladium-based three-component catalyst, the selective formation of methanofullerenes was observed.…”
Section: Reactions With Aromaticsmentioning
confidence: 99%
“…288−295 In general, these reactions are carried out thermally, and reactions with C 60 fullerene result in a mixture of three regioisomers, identified as the [6,6]-closed methanofullerene and the two [5,6]-open fulleroids. 296 Recently, Tuktarov and co-workers investigated cycloaddition of diazothioates to C 60 under thermal and catalytic conditions. 295 It was found that, in the presence of a palladium-based three-component catalyst, the selective formation of methanofullerenes was observed.…”
Section: Reactions With Aromaticsmentioning
confidence: 99%
“…[106][107][108][109] Unlike pristine fullerene, with limited solubility in organic solvents, upon derivatization the grafted functional groups onto the fullerene's cage not only improves the solubility of fullerene but also provides additional reaction sites for further covalent hybridization with graphene. [106][107][108][109] Unlike pristine fullerene, with limited solubility in organic solvents, upon derivatization the grafted functional groups onto the fullerene's cage not only improves the solubility of fullerene but also provides additional reaction sites for further covalent hybridization with graphene.…”
Section: Covalent Hybrids Of Fullerene Derivatives and Graphenementioning
confidence: 99%
“…Carbene additions to fullerenes have already attracted considerable attention. 8 Carbenes should also play a similar role in interstellar chemistry. 37 Our experiments demonstrate the reactivity of C 60 (C:) n toward H 2 and H 2 O.…”
mentioning
confidence: 99%